Experimental determination of thermal expansion of natural MoS2. (4th May 2018) - Anemone, Gloria; Al Taleb, Amjad; Castellanos-Gomez, Andres; Farías, Daniel
Abstract: We report helium diffraction from natural MoS2 single crystal. The high quality of the samples studied lead to the appearance of sharp and intense in-plane and out-of-plane diffraction peaks, with unusually low background. The pronounced out-of-plane features observed confirm the high corrugation of the 2D surface unit cell. The observation of diffraction features along the two main high symmetry directions allows determining the in-plane surface lattice constant with high accuracy. The measured lattice constant along and is Å. Within experimental error, the MoS2 lattice parameter was found to remain constant in the temperature range between 90 and 522 K, in good agreement with previously reported DFT based calculations.